Dynamic Response of a Beam Resting on a Nonlinear Foundation to a Moving Load: Coiflet-Based Solution - Piotr Koziol; Zdzislaw Hryniewicz (Shock and Vibration)
This paper presents a new semi-analytical solution for the Timoshenko beam subjected to a moving load in case of a nonlinear medium underneath. The finite series of distributed moving loads harmonically varying in time is considered as a representation of a moving train. The solution for vibrations is obtained by using the Adomian's decomposition combined with the Fourier transform and a wavelet-based procedure for its computation. The adapted approximating method uses wavelet filters of Coiflet type that appeared a very effective tool for vibration analysis in a few earlier papers. The developed approach provides solutions for both transverse displacement and angular rotation of the beam, which allows parametric analysis of the investigated dynamic system to be conducted in an efficient manner. The aim of this article is to present an effective method of approximation for the analysis of complex dynamic nonlinear models related to the moving load problems.